Potato Starch for Enhancing the Properties of the Drilling Fluids - Assi, Amel Habeeb (Iraqi Journal of Chemical and Petroleum Engineering, 2018)
Different additives are used in drilling fluids when the demanded properties cannot be gotten with clays. Drilling muds needs several additives and materials to give good characteristics. There are local alternatives more suitable for enhancing the rheology and filtration of drilling fluids. An experimental work had been conducted to assess the suitability of using potato starch to enhance rheological properties and filtration in drilling mud. This study investigated the potato starch as a viscosifier and fluid losses agent in drilling fluid. Results from this study proved that rheological properties of potato starch mud increased when pH of drilling fluid is increased. Potato starch could be used to enhance gel strength at low pH (approximately 8.6) and viscosifir at high pH mud (approximately 10.8). The experimental work show that the optimum NaOH concentration was between (2-6) lb./bbl and if more than that concentration was used, the relation between pH and plastic viscosity would be inversed. Comparative analysis of mud properties obtained from the potato starch and starch at low pH showed good rheological properties of the starch than for potato starch, while at high pH, both of them nearly showed good rheological properties. In conclusion, potato starch reduced filtration rate of fluid and improved the characteristics and consistency of mud cake as a primary function and showed an effect on the fluid rheology as a second function.